Literature Review: Air Oxygen Level Monitoring System - Agustinur, Satya Cantika; Khalifa, Khaled Issa; Yantidewi, Meta; Deta, Utama Alan (International Journal of Research and Community Empowerment, 2023)
Oxygen is a very important gas for humans. The need for oxygen around the plant is very low because the exhaust gas from various factories often becomes pollutants, one of which is the cement industry. The oxygen content needs to be known so that the level of vigilance of workers and the community is higher. For this reason, it is necessary to make a monitoring device for oxygen content. In this view will be discussed several gas sensors, especially oxygen sensors. In addition, Arduino microcontrollers and Raspberry Pi microprocessors were also discussed. The goal is to be able to determine the type of oxygen sensor as a detector of oxygen levels in the air. The discussion of microcontrollers and microprocessors is also a determinant of the motherboard connected to the oxygen sensor. Thus, the explanation of this review can be used to develop a monitoring system for oxygen content in the air.  The research method used is in the form of literature studies. Literature study is the process of finding research data or information by reading scientific journals, reference books, and articles about oxygen content monitoring devices. This tool functions as a gas analyzer by choosing the MQ-135 sensor as an oxygen sensor because it is more affordable and easy to obtain which is supported by the Raspberry Pi device.